Platelets in Viral Infections – Brave Soldiers or Trojan Horses - Schrottmaier, Waltraud C.; Schmuckenschlager, Anna; Pirabe, Anita; Assinger, Alice (Frontiers in Immunology, 2022)
Viral infections are often associated with platelet activation and haemostatic complications. In line, low platelet counts represent a hallmark for poor prognosis in many infectious diseases. The underlying cause of platelet dysfunction in viral infections is multifaceted and complex. While some viruses directly interact with platelets and/or megakaryocytes to modulate their function, also immune and inflammatory responses directly and indirectly favour platelet activation. Platelet activation results in increased platelet consumption and degradation, which contributes to thrombocytopenia in these patients. The role of platelets is often bi-phasic. Initial platelet hyper-activation is followed by a state of platelet exhaustion and/or hypo-responsiveness, which together with low platelet counts promotes bleeding events. Thereby infectious diseases not only increase the thrombotic but also the bleeding risk or both, which represents a most dreaded clinical complication. Treatment options in these patients are limited and new therapeutic strategies are urgently needed to prevent adverse outcome. This review summarizes the current literature on platelet-virus interactions and their impact on viral pathologies and discusses potential intervention strategies. As pandemics and concomitant haemostatic dysregulations will remain a recurrent threat, understanding the role of platelets in viral infections represents a timely and pivotal challenge.